Bacteria Magz as an Alternative Learning Resource on Bacteria Concept for Senior High School Level - Ewi Awaliyati; Rida Oktorida Khastini; Ika Rifqiawati; Indah Juwita Sari (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This study aimed to determine the feasibility of Bacteria magz as alternative learning resources on the bacteria concept of senior high school. The method used in this research is a product feasibility test using a Likert scale. We used three experts to validate the Bacteria magz that have an expertises and experiences in learning media, bacteria concept, and alternative learning sources. The results of the expert test evaluation on the aspect of the media were 93,25%, while on the material aspect was 87,5%. The average value of the Bacteria magz as alternative learning sources was 90,37%. The Bacteria magz as alternative learning resources on bacteria concept was very suitable for ten grade students of senior high school.